Albumin to creatinine ratio in a random urine sample: Correlation with severity of preeclampsia (Latakia University Journal -Medical Sciences Series, 2018)
Introduction : 24-h urine protein is traditionally used as a gold standard method for protein estimation. Because of the operational difficulty, there is the necessity to use rapid, convenient, and reliable method of proteinuria estimation in pregnant women with preeclampsia. Aim : To investigate the role of albumin to creatinine ratio in a random urine sample for diagnosis and assessment of severity of preeclampsia. Materials and Methods :This is a prospective study conducted at Obstetrics and Gynecology Department at Tishreen University Hospital , Lattakia , Syria , during the period between March 2016 and May 2017. Two separate groups, 30 women each, were enrolled. All were pregnant at their third trimester with confirmed preeclampsia . Based on their blood pressure levels, Group A, included patients with non severe form of preeclampsia, whereas group B included cases with severe one . Albumin to creatinine ratio (ACR) in random urine samples and the 24-h protein content in urine were assessed . Results : ACR and the 24-h urine protein excretion were significantly correlated, (r =0.901 , p< 0.001). Cut-off value for ACR for this group of patients was calculated to be 300 mg/g , above which severity of the disease is highly probable . The sensitivity and specificity were 100% and 59%, respectively. The positive predictive value was 75% and negative predictive value was 100%. Conclusion : Random urine ACR may be a reliable method for prediction and assessment of severity of preeclampsia. تحري دور نسبة الألبومين إلى الكرياتينين في عينة بول عشوائية في تقييم شدة الانسمام الحملي مقدمة : لطالما استُخدم جمع بول 24 ساعة بشكلٍ تقليديٍّ كمعيارٍ ذهبي لتشخيص البيلة البروتينية عند الحوامل, و نظراً للصعوبات المتعلقة بإجرائه , دعت الحاجة لاستخدام طرقٍ سريعةٍ , مريحةٍ و ذات موثوقيةٍ لتشخيص البيلة البروتينية عند الحوامل المصابات بما قبل الإرجاج. هدف البحث : هدفَ هذا البحث لدراسة دور نسبة الألبومين إلى الكرياتينين في عينة بول عشوائية في تشخيص و تقييم شدة ما قبل الإرجاج . المواد و الطرق : أجريت دراسة مستقبلية في قسم التوليد و أمراض النساء في مشفى تشرين الجامعي , اللاذقية , سوريا , في الفترة الممتدة ما بين آذار 2016 و أيار 2017 . شملت هذه الدراسة مجموعتين من المرضى , كل مجموعة مؤلفة من 30 مريضة . جميع المريضات كنُّ حوامل في الثلث الثالث من الحمل مع تشخيص مُثبت لما قبل الإرجاج . بالاعتماد على قيمة التوتر الشرياني , ضمت المجموعة الأولى مريضات ما قبل الإرجاج غير الشديد, في حين ضمت المجموعة الثانية مريضات ما قبل الإرجاج الشديد. تم قياس نسبة الألبومين إلى الكرياتينين في عينة بول عشوائية و كمية البروتين في بول 24 ساعة . النتائج : أظهرت هذه الدراسة وجود ترابط هام بين نسبة الألبومين / الكرياتينين في عينة البول العشوائية من جهةٍ و إطراح البروتين في بول 24 ساعة من جهةٍ أخرى (r =0.901 ) (P<0.05) . تم حساب القيمة الحدية لنسبة الألبومين إلى الكرياتينين في هذه الفئة من المرضى و كانت 300 مغ/غ , حيث أن النسب فوق هذه القيمة الحدية تعكس احتمالاً مرتفعاً لما قبل الإرجاج الشديد , مع حساسية 100% , نوعية 58% , قيمة تنبؤية إيجابية 75%, قيمة تنبؤية سلبية 100% . الخلاصة : إن نسبة الألبومين إلى الكرياتينين في عينة بول عشوائية هي طريقة يمكن الاعتماد عليها لتشخيص و تقييم شدة ما قبل الإرجاج .